repressions - Grigoryeva, Elena (project baikal, 2017)
The point at issue is not their good intentions (of those who have any), but the objective significance of their policy, i.e., what its results are, cui prodest – whom it benefits, to whose mill it actually brings grist. (V. I. Lenin, A Talk 0n “Cadet-Eating”) It seems that a terrible page of the “Big Terror” was turned over long ago. We can forget it and move on. But it fails. There are still certain people in our country who keep to the principle “no man /monument / cultural heritage site – no problem”. The terror aimed against cultural values still exists in our days. A new book about the purged architect Kasimir Mital was published just before annihilation of his constructivist offspring: the Hotel Sibir located in the center of Irkutsk is being purposefully deleted from the heritage list.